Instantly personalised face masks - Quek, Nico Ping Yang (Nanyang Technological University, 2021)
In this project, we will use a novel material to achieve instant personalized facial masks via 4D printing. The mask will be shaped to fit the face of a particular individual in a couple of minutes.